Pengaruh Aktivitas Fisik dan Jumlah Asupan Makan terhadap Gangguan Siklus Menstruasi pada Atlet Voli Usia Remaja di Kabupaten Kudus - Vella Nevyta, Puan; Widiasih, Esti; Anggraeni Noviasari, Nina (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Menstrual cycle disorders can negatively impact athletic performance. A combination of irregular eating patterns and intense training can increase the risk of such disturbances. Factors influencing menstrual cycle irregularities include nutritional status, physical activity, dietary habits, stress levels, smoking, hormonal medication use, and endocrine disorders. A study conducted in Semarang found that 28.8% of female athletes experienced menstrual cycle issues. This research aims to investigate how physical activity and food intake affect menstrual cycle disorders among adolescent volleyball athletes in Kudus Regency. The methodology employed was an observational analytical study with a cross-sectional approach, selecting 46 respondents using purposive sampling techniques. The IPAQ and SQFFQ questionnaires were used as research instruments. Data were analyzed using bivariate analysis with the Chi-Square test. The results indicated that the majority of athletes had a high level of physical activity (76.1%), while 50% were categorized as having severe food intake deficits. Additionally, 78.3% of athletes experienced menstrual cycle disturbances, which included 36 individuals. Bivariate analysis revealed that physical activity influenced the menstrual cycle of adolescent volleyball athletes (p-value = 0.045), and dietary intake also had an effect (p-value = 0.000). Therefore, both physical activity and eating patterns significantly impact menstrual cycle disorders among adolescent volleyball athletes.